Controllable assembly of Pd nanosheets: a solution for 2D materials storage. Issue 25 (12th June 2017) - Shan, Hao; Liu, Lei; He, Jiaqing; Zhang, Qing; Chen, Wenlong; Feng, Rui; Chang, Chao; Zhang, Peng; Tao, Peng; Song, Chengyi; Shang, Wen; Deng, Tao; et al.
Abstract : We develop a reversible assembly/diassembly methodology to preserve the 2D structures and functions of Pd nanosheets by assembling them into stacks and obtain the desired 2D structure and ultimate performance of MOR. Abstract : Two-dimensional (2D) materials have attracted wide attention in photonic, electric, catalysis, and energy fields. Compared to the gas phase synthesis, the liquid phase route enables mass production of 2D materials with relatively low costs. However, these free-standing 2D materials obtained via the wet chemical route have a strong tendency to stack on each other; moreover, their 2D structure and the relevant functions degrade over time. Thus, we developed a strategy to achieve the reversibility of assembly/disassembly in Pd nanosheets (NSs) by utilizing anionic/cationic surfactants. Based on this methodology, the 2D structure of free-standing Pd NSs can be preserved with excellent performances for long-term use. Our results showed that free-standing Pd NSs were extremely unstable and decomposed into nanoparticles in 9 days. However, the assembled Pd NSs stacks maintained their 2D structure and preserved the methanol oxidation reaction (MOR) properties after disassembling.